Biochemical engineering journal (Elsevier, 1998)
"The Biochemical engineering journal aims to promote progress in the crucial chemical engineering aspects of the development of biological processes associated with everything from raw materials preparation to product recovery, relevant to industries as diverse as medical/healthcare, food and environmental protection."
Keywords: Biochemical engineering : Periodicals; Génie biochimique : Périodiques; Biochemical engineering